Carbon accumulation and soil assessment of an early stage rehabilitated tropical forest - Ch'ng, Huck Ywih (2011)
Logging and shifting cultivation negatively affect initial soil carbon (C) storage especially at the initial stage of deforestation as such practices lead to global warming. Thus, afforestation programme is needed to mitigate this problem. Many studies have been reported to estimate regional C storage and national C budgets of temperate forests in many countries but little is known about the trend of soil C accumulation and soil fertility for forest regrowth in relation to an initial stage of rehabilitated forests in the tropics such as Malaysia. Information on C accumulation and soil fertility for forest regrowth of rehabilitated forests suggest whether these forests can serve as C sink to mitigate climate change. Thus, the objective of this study was to determine the soil C accumulation quantitative and qualitatively, and soil fertility of an early stage of a rehabilitated forest. The study was conducted in a rehabilitated forest of Universiti Putra Malaysia, Bintulu Sarawak Campus area (Latitude 03o12 N and Longitude 113o02 E at 50 m above sea level) with the mean annual rainfall, relative humidity and temperature of 2933 mm, 80%, and 27 oC respectively. The area was previously abandoned after shifting cultivation activity and it has been rehabilitated since 1991 by planting indigenous timber species from the family Dipterocarpaceae and Non-Dipterocarpaceae. The size of each experimental plot was 30 x 40 m. Soil samples were collected randomly using a mineral soil auger from 1- to 7-year-old rehabilitated forest at 0-20, 20-40, and 40-60 cm depths. Ten samples were collected from each depth per plot and each sample was a bulk of three samples. These soil samples were air dried, crushed manually, and sieved to pass a 2-mm sieve, after which they were transferred into plastic bags and labelled. The soil texture of the rehabilitated forest was Typic Paleudalts and is a typical of Ultisols, which is characterized by the coarse loamy yellow podzolic group that developed from weathering of sandstone. The procedures outlined in the Materials and Methods section were used to analyze the soil samples for pH, total C, soil organic matter (SOM), total nitrogen (N), C/N ratio, yield of humic acid (HA), and soil stable C from humic acids (CHA). The bulk densities at these depths were determined by the coring method. The bulk density method was used to quantify soil total N stocks, soil total C, SOM, HA, and CHA at the stated sampling depths on per hectare basis. The first study determined the soil C accumulation of an early stage of a rehabilitated forest. Results showed that pH decreased significantly with increasing age of rehabilitated forest regardless of depth. SOM and total C contents increased with age. No significant difference in the quantity of CHA content for the different ages of rehabilitated forest at 0-20, 20-40 and 40-60 cm soil were observed. Since the CHA is more stable, it is more realistic to quantify the amount of C accumulated in setting up the rehabilitated forest at initial stages. The second study qualitatively assessed the initial soil C accumulation of the rehabilitated forests using Fourier Transform Infrared spectroscopy (FTIR). The spectra of all locations were similar because there was no significant difference in the quantities of CHA regardless of forest age and soil depth. The spectra showed distinct absorbance at 3290, 1720, 1630, 1510, 1460, 1380 and 1270 cm-1. Increase of band at 1630 cm-1 and 1510 cm-1 from 0-20 cm to 40-60 cm were observed, suggesting C decreased down the depths of 20-40 cm and 40-60 cm. However, the CHA in the soil depths were not different. The band at 1630 cm-1 was assigned to carboxylic and aromatic groups. Increase in peak intensity at 1510 cm-1 was because C/N ratio increased with increasing soil depth. This indicates that decomposition rate decreased with increasing soil depth and but decreased with stable C. FTIR allows qualitative identification of functional groups and thus providing a better understanding of decomposition pathways of soil organic matter and C build up. The third study assessed the initial soil fertility by comparing the soil factors of different ages of the rehabilitated forest. The SEF values of the rehabilitated forest showed low fertility and showed slight increase with increasing depth. In the depths of 20-40 and 40-60 cm, SEF values were high due to nutrient absorption of tree roots and nutrient leaching. Nutrients such as potassium (K), aluminium (Al), and SOM were found to be important variables influencing trees growth rate in this nutrient poor soil. Al and SOM in particular, had significant influence on the soil fertility and thus may have effect on the tree growth rate in this poor fertility site. Low SOM content and coarse sand soil texture caused nutrients to leach rapidly in Ultisols, thus causing soils to be poor in plant nutrients. The SEF used in this study allows comparative analysis of soil fertility and evaluation and identification of soil conditions among initial ages of rehabilitated forests. Overall, this study did not show any significant statistical accumulation in the soil C stocks up to 7-year-old rehabilitated forest and this was mainly due to the supply of raw materials since the trees were considered as immature stage (1- to 7-year-old) in comparison to a continuous supply of organic matter from mature vegetation in the existing older stand of rehabilitated forest and secondary forest. This clearly shows that afforestation program requires a long period (20 years) to recover the C stocks in soil and it is serious to clear the forest for unsustainable land usage.